Penerapan Model Kooperatif Tipe Teams Game Tournament Dengan Media Scavenger Hunt Untuk Meningkatkan Hasil Belajar Sejarah Pada Siswa Kelas X IPS Di SMA Negeri 3 Kupang Timur - Rocky, Julian Hermando; Djakariah, Djakariah; Utomo, Susilo Setyo; Neolaka, Stefridan Yantus (FLORESIENSIS, 2024)
The purpose of this study was to improve history learning outcomes by applying a tournament teamwork model using a treasure hunt medium. The type of research used was classroom action research (CAR). The results of the first cycle test showed that 21 students who completed the task had a presentation (60%), while 14 students who did not complete it had a presentation (40%). Based on the analysis of the 35 students who took the cycle II exam, 29 students completed their presentations (83%). From these results, the researcher stated that the classroom action study was terminated because the compliance target had been achieved, and it could be concluded that the application of the cooperative team tournament game model with treasure hunt media could improve history learning outcomes in 10th grade social studies students at SMA Negeri 3 Kupang Timur